Does Rising R&D Investments Increase the Academic Patent Registration? - Barcziová Anikó; Bálintová Monika; Machová Renáta; Bálintová Mónika; Балінтова М.; Bálintová М. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. The aim of the research paper is to study and analyze academic patent registration in four countries of the European Union. In the research paper we identify the importance of academic patents and the action of knowledge-transfer. Moreover, we work with the phrase of academic patent registration rate. The reason of calculating with academic patent registration rate, is to receive the best quality calculations and comparations possible. Due to the fact, that the analyzed countries´ population number is different, we cannot compare academic patent registration number among them. One of the main goals of our research paper is to study, if there can be found a significant connection between the academic patent registration rate and the amount of the national research and development (R&D) investment in the selected countries. R&D expenditure is the percentual rate of money which countries have invested into research and development from their annual gross domestic product (GDP). We study and work with four selected countries of the EU, concretely Sweden, Denmark, Austria and Hungary. It means, we compare two different regions of the EU, northern countries with central EU countries. However, it is extremely important not to forget about the historical and cultural background of the mentioned studied areas, because those factors can highly influence the current behavior even in the mentioned research area. Theoretically, the nationally annually invested amount of money into R&D has a supportive role on the knowledge-transfer process of the country, and also should increase the number of academic registered patents. However, is the mentioned statement true and correct for the analyzed four countries? With our compressional research we realized that rising R&D investments do not have a positive effect on the academic patent registration rate. In three countries out of four, it was correct. However, in Sweden while the R&D expenditure was stagnating, the academic patent registration rate has shown a positive rise. We need to emphasize, that our analyzes do need further continuation of the research. Since we cannot make strong general statements, based on only four countries.

A kutatás célja az akadémiai szabadalmak regisztrációjának tanulmányozása és elemzése az Európai Unió négy országában. A cikkben azonosítjuk az akadémiai szabadalmak fontosságát és helyüket a tudástranszferbe. Az akadémiai szabadalmi lajstromozási aránnyal való számítás célja, hogy a lehető legjobb minőségű számításokat és összehasonlításokat kapjuk a kutatásunk alpján. Tekintettel arra, hogy a vizsgált országok népességszáma eltérő, az akadémiai szabadalmi bejegyzési számot nem tudjuk összehasonlítani közöttük. Kutatásunk egyik fő célja annak vizsgálata, hogy van-e szignifikáns összefüggés az akadémiai szabadalmak regisztrációs aránya és a nemzeti kutatásfejlesztési (K+F) beruházások mértéke között a kiválasztott országokban. A K+F ráfordítás az a százalékos értékarány, amelyet az országok éves bruttó hazai termékükből (GDP) a kutatásba és fejlesztésbe fektettek be. Az EU négy kiválasztott országát elemezzük, konkrétan Svédországot, Dániát, Ausztriát és Magyarországot. Ez azt jelenti, hogy az EU két különböző régióját, az északi országokat a középső EU-országokkal hasonlítjuk össze. Kiemelten fontos azonban, hogy ne feledkezzünk meg az említett vizsgált területek történelmi és kulturális hátteréről, mert ezek a tényezők nagymértékben befolyásolhatják a jelenlegi helyzetet még az említett kutatási területen is. Elméletileg az országosan évente K+F-be fektetett pénzösszegnek támogató szerepe van az ország tudástranszferében, és növelnie kell az akadémiai bejegyzett szabadalmak számát is. Igaz és helytálló azonban az említett állítás az elemzett négy országra? Kompressziós kutatásunkkal rájöttünk, hogy a növekvő K+F beruházásoknak nincs pozitív hatása az akadémiai szabadalmak regisztrációs arányára. Négy országból háromban helyes volt feltevésünk. Svédországban azonban, miközben a K+F kiadások stagnáltak, az akadémiai szabadalmak regisztrációs aránya pozitív emelkedést mutatott. Hangsúlyoznunk kell, hogy elemzéseink a kutatás további folytatását igénylik, mivel nem tudunk határozott általános kijelentéseket tenni, mindössze négy ország alapján.

Резюме. В статті за мету поставлено дослідження та аналіз академічної реєстрації патентів у чотирьох країнах Європейського Союзу. За результатами проведних досліджень визначено важливість академічних патентів і дії з передачі знань. Дослідження ґрунтується на аналізі академічної реєстрації патентів як відносного показника, який дозволяє отримувати найкращі розрахунки та порівнювати різні країни з урахуванням їх населення. Однією з головних цілей дослідницької роботи є дослідження того, чи можна знайти значний зв’язок між рівнем реєстрації академічних патентів і обсягом національних інвестицій у дослідження та розробки (НДДКР) у вибраних країнах. Витрати на НДДКР – це відсоток грошей, які країни інвестували в дослідження та розробки від свого річного валового внутрішнього продукту (ВВП). Для дослідження було обрано чотири європейські країни, а саме Швецію, Данію, Австрію та Угорщину, з двох різних регіонів ЄС – північної та центральної частин ЄС. Було також враховано історичне та культурне походження згаданих досліджуваних територій, оскільки ці фактори можуть сильно впливати на поточну поведінку навіть у згаданій досліджуваній території. Теоретично, щорічно інвестована сума грошей у дослідження та розробки в певній країні відіграє допоміжну роль у процесі передачі знань у країні, а також має збільшити кількість академічних зареєстрованих патентів. Проте, чи є зазначене твердження правдивим і правильним для аналізованих чотирьох країн? Проведене дослідження встановило, що зростання інвестицій у НДДКР не має позитивного впливу на рівень реєстрації академічних патентів. Ця гіпотеза була підтверджена в трьох країнах з чотирьох. Однак у Швеції, поки витрати на дослідження та розробки стагнували, рівень реєстрації академічних патентів продемонстрував позитивне зростання. Необхідно підкреслити, що отримані результати потребують подальшого продовження досліджень, оскільки не можна робити узагальнення, базуючись лише на чотирьох країнах.
Чи зростання інвестицій в НДДКР збільшує реєстрацію академічних патентів?
A K+F-be való növekvő befektetések növelik-e az akadémiai szabadalmak regisztrációját?
https://aab-economics.kmf.uz.ua/aabe/issue/view/1
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010507
Keywords: patent; academic patent; R&D; investment; per capita patent registration rate